Effect of yeast extract concentration on lactate production - Rubena Malfia, Binti Kamaldin. (Universiti Malaysia Sarawak (UNIMAS), 2004)
In this study, the effects of east extract at different concentration (0 giL, 2g1L, 5g1L, and 10gIL) was examined for the production of lactate by Lactococcus lactis 10-1. The batch fermentation processes was conducted at initial pH6, temperature of 370 C and agitate at 200 rpm. The pH was uncontrolled throughout the study. The fermentation was carried out using the shake flasks. From the result obtained, there is not much different on lactate concentration at different yeast extract concentration. However, at 0 giL yeast extract concentration, the fermentation efficiency was 45.45% higher compared to at 2g1L yeast extract concentration which was 38.92%, at 5g1L yeast extract concentration was 36.66% and at 10 giL yeast extract was 22.57%. Overall, when concentration of yeast extract is lower, it will result in higher residual glucose, thus needed longer period for complete consumption.